PENGEMBANGAN ECOTOURISM MELALUI LOCAL CULTURE ADVANTAGE PADA DESTINASI WISATA DANAU TOBA - Sianturi, Riko Fridolend; Sitompul, Pandapotan (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
In preserving the natural environment and improving the welfare of local communities, ecotourism development is needed through the involvement of local culture. Ecotourism development is an important note to realize Lake Toba as a classy destination and viewed by the world, because the values ​​obtained will realize sustainable development, introduce culture and improve the economy, especially the local community. The involvement of local culture is a buffer for developing the sustainability of ecotourism in promoting and increasing the number of tourist visits. One of the efforts often made by local culture to develop ecotourism through rituals or traditional ceremonies, by introducing traditions and customary norms that are owned, there needs to be a more in-depth study or research with the aim of assessing the potential for ecotourism development, identifying the level of influence and importance of stakeholders, analyzing benefits and trends as well as strategies for developing and managing ecotourism. Data collection was carried out by interviews, observations, and literature searches. The analysis used was the Analysis of Operational Areas located in the ecotourism area, analysis of the level of influence and interests of local culture in the involvement of developing ecotourism using qualitative descriptive analysis techniques. The results of the study showed that Ecotourism is worthy of being developed as a long-term investment. The involvement of local culture as the main key player in introducing ecotourism. Local cultural involvement provides benefits to improve socio-economic. Ecotourism development strategies can adopt collaboration involving traditional figures who are at the forefront of introducing ecotourism.